Metachromasia for blood basophils identification in hybrid surubim catfish: Methodological contribution - De Pádua, Santiago Benites [UNESP]; Ishikawa, Márcia Mayumi (My University, 2011)
Different protocols of fixation and hydrolysis of blood smears of hybrid surubim catfish for metachromasia to marking blood basophils were evaluated. For this reason, methanol, acid-alcohol and formalin vapor were tested as fixatives. For hydrolysis of blood smears, HCl, citric acid and 2-Mercaptoethanol + Urea + NaCl solutions was evaluated. After procedures, the blood smears was stained with toluidine blue (0.025%) diluted in McIlvaine buffer (pH 4). The different protocols for fixation and hydrolysis of blood smears for metachromasia influenced the quality of the reaction. Hydrolysis with 2-Mercaptoethanol + Urea + NaCl solutions provided negative results when using methanol and acid-alcohol as fixatives. The fixation with acid-alcohol associated with citric acid hydrolysis provides highest quality reason.
Metacromasia para identificação de basófilos sanguíneos em surubim híbrido: Contribuição metodológica
Keywords: Basophils marking; Cytochemistry; Fish hematology; Toluidine blue